Nilai-Nilai Filosofi Ornamen Di Pura Dalem Segara Madhu Desa Jagaraga Kecamatan Sawan Kabupaten Buleleng - I Made Gami Sandi Untarra; Ayu Veronika Somawati (Jayapangus Press, 2023)
One of the parts that can be the hallmark of a temple is the carved ornaments. Ornaments in sacred buildings, especially temples, of course contain very deep philosophical values. In general, ornaments at temples, especially Dalem Temple, are related to wayang reliefs, reliefs that tell about the final journey of humans and so on. This is different from the ornaments found in Pura Dalem Segara Madhu. the uniqueness of Pura Dalem Segara Madhu Jagaraga Village can be seen in the reliefs located on the walls of the temple's penyengker. The relief depicts the history of Balinese people against Dutch colonialism. There are also reliefs depicting ships being attacked by sea monsters, people driving cars and so on. The uniqueness of the ornaments owned by Pura Dalem Segara Madhu Jagaraga Village is an interesting thing to study regarding the philosophical values contained therein. In general, this study aims to understand the value of Hindu philosophy in ornaments at Pura Dalem Segara Madhu, Jagaraga Village, Sawan District, Buleleng Regency. This type of research is qualitative using descriptive qualitative methods and data collection techniques using observation, interviews, literature and documentation. The results of the study regarding this matter are that all the reliefs contained in Pura Dalem Segara Madhu Jagaraga have a connection with one another regarding the struggles of the Jagaraga Village community. This reaffirms that this temple is not only related to the spiritual life of the people, but also related to the history of the people's struggle which is the spirit of social life.